Burner-heated dehydrogenation of a liquid organic hydrogen carrier (LOHC) system - Bollmann, Jonas; Mitländer, Kerstin; Beck, Dominik; Schühle, Patrick; Bauer, Florian; Zigan, Lars; Wasserscheid, Peter; Will, Stefan (International Journal of Hydrogen Energy, 2023)
For a hydrogen-based economy, safe and efficient hydrogen storage is essential. Compared to other chemical hydrogen storage technologies, such as ammonia or methanol, liquid organic hydrogen carrier (LOHC) systems allow for a reversible storage of hydrogen while being easy to handle in a diesel-like manner. In our contribution, we describe for the first time the successful utilization of the exhaust gas enthalpy of a porous media burner to directly supply the dehydrogenation heat for a kW-scale dehydrogenation of the hydrogen-rich LOHC compound perhydro dibenzyltoluene (H18-DBT). Our setup demonstrates the dynamics of the dehydrogenation unit at a realized maximum hydrogen power of 3.9 kWth, based on the lower heating value of the released hydrogen. For the intended applications with fluctuating hydrogen demand, e.g. a hydrogen refueling station (HRS) or stationary heating in buildings, a dynamic hydrogen supply from LOHC is important. Methane, e.g. from a biogas plant, is utilized in our scenario as a fuel source for the burner. Hydrogen is released within 30 min after cold start of the system. The dehydrogenation unit exhibits a power density relative to the reactor volume of about 0.5 kWtherm l−1 based on the lower heating value of the hydrogen and a catalyst productivity of up to 0.65 gH2 gPt−1 min−1 for hydrogen release from H18-DBT. An analysis of the by-products and reaction intermediates shows low by-product formation (e.g. maximum 0.6 wt.-% for high boilers and 0.9 wt.- % for low boilers) and uniform distribution of intermediates after the reaction. Thus, a relatively homogeneous temperature distribution and a uniform LOHC flow in the reaction zone can be assumed. Our findings illustrate the dynamics (heating rates of about 10 K min−1) and performance of direct heating of a release unit with a burner and represent a significant step towards LOHC-based hydrogen provisioning systems at technically relevant scales.
CRIS-Team Scopus Importer:2023-09-01
Keywords: Dehydrogenation; Dynamic heat supply; Hydrogen storage; LOHC; Porous media burner

Chloroorganic impurities in technical-grade benzyltoluene – Influence on its use as LOHC compound and removal strategies - Henseler, J.; Rullo, F.; Mitländer, Kerstin; Johner, N.; Wolf, P.; Schühle, Patrick; Geißelbrecht, M.; Wasserscheid, P. (International Journal of Hydrogen Energy, 2024)
The benzyltoluene (H0-BT)/perhydro benzyltoluene (H12-BT) LOHC system is very attractive for large-scale hydrogen storage and transportation applications due to its fuel-like handling and excellent technical availability. H0-BT is applied in industrial quantities since the 1960′ies as heat trafer fluid and is technically produced by a Friedel-Crafts alkylation of chlorobenzene and toluene. However, the current production route leads to minor impurities of chloroorganic compounds in technical H0-BT that were found to severely harm the performance in the catalytic hydrogenation to H12-BT, i.e. in the hydrogen charging process of the respective LOHC storage cycle. Our contribution deals with three aspects of this practically highly relevant topic: a) It discloses the previously unknown chemical structure of the relevant chloroorganic impurities; b) it develops a process for their removal by adsorption and/or hydrodechlorination using a commercial Ni/SiO2–Al2O3 material, and c) it determines the performance difference of the so-purified H0-BT samples and H0-BT samples containing the relevant chloroorganic compounds in the catalytic hydrogenation of H0-BT to H12-BT.
CRIS-Team Scopus Importer:2024-02-02
Keywords: Benzyltoluene; Catalyst poisoning; Chloroorganic compounds; Hydrodechlorination; Hydrogenation; Impurities; LOHC

Continuous (hydro-)dechlorination of aromatic chloride compounds in benzyltoluene - Mitländer, Kerstin; Henseler, J.; Rullo, F.; Nathrath, Phillip; Geißelbrecht, M.; Wasserscheid, Peter; Schühle, Patrick (International Journal of Hydrogen Energy, 2025)
Benzyltoluene is an attractive liquid organic hydrogen carrier (LOHC) compound but needs to be purified after its technical synthesis to remove chloride impurities that would harm the Pt-based hydrogenation and dehydrogenation catalysts used for the reversible LOHC loading and unloading with hydrogen. For this purpose the dechlorination of chlorobenzyltoluene in a benzyltoluene matrix was studied in a continuously operated trickle bed reactor using a commercially available nickel catalyst. The results indicate that the removal of chlorobenzyltoluene is mainly adsorption based. Rapid aging experiments with purposely added chloroaromatic compounds (chlorobenzene and chloronaphthalene) in quantities of up to 9000 ppm suggest that high chloroaromatic loadings lead to reduced dechlorination activity due to a rapid blocking of active sites. The dechlorination capacity per gram of the used catalyst material was determined to be in the range of 2 kg of technical benzyltoluene.
CRIS-Team Scopus Importer:2025-04-25
Keywords: Benzyltoluene; Chloroaromatics; Chlorobenzene; Dechlorination; LOHC

Gas-Phase Hydroformylation Using Supported Ionic Liquid Phase (SILP) Catalysts - Influence of Support Texture on Effective Kinetics - Schörner, Markus; Rothgängel, Philipp; Mitländer, Kerstin; Wisser, Dorothea; Thommes, Matthias; Haumann, Marco (ChemCatChem, 2021)
The supported ionic liquid phase (SILP) concept, which included thin films of ionic liquid dispersed onto porous support surfaces, was applied for the gas-phase hydroformylation of but-1-ene catalyzed by Rh-bpp (bpp=biphephos ligand) complexes. The support material silica was carefully pre-treated by a hydrothermal procedure to induce textural changes concerning the pore size. Starting with a mean pore size of 3 nm these could be enlarged by almost a factor of 10 up to 27 nm. Different particle size fractions having the same pore size of 10 +/- 1 nm were investigated regarding the hydroformylation activity. A clear limitation by pore diffusion can be found for particles larger than 500 mu m in diameter. The limitation could be minimized by enlarging the pore size. To support the data, dimensionless numbers and criteria were calculated, including Thiele-modulus, Mears, and Weisz-Prater. All data support the assumption that limitation occurs around 500 mu m particle size if 10 nm pores are present.
CRIS-Team WoS Importer:2021-08-27

Silicon Carbide Supported Liquid Phase (SLP) Hydroformylation Catalysis – Effective Reaction Kinetics from Continuous Gas-phase Operation - Schörner, Markus; Mitländer, Kerstin; Wolf, Moritz; Franke, Robert; Haumann, Marco (ChemCatChem, 2022)
The hydroformylation reaction is one of the most important applications of homogeneous catalysis on an industrial scale with worldwide production capacities exceeding 15 Mio tons per year. Efficient catalyst immobilization becomes mandatory for such large-scale processes. In this work, a supported liquid phase (SLP)-type catalyst on a silicon carbide support material was applied in the continuous Rh-bpp (bpp=biphephos) catalyzed gas-phase hydroformylation of but-1-ene. A parameter variation was carried out in the pressure range from 0.5 to 3.0 bara for but-1-ene, 0.5 to 5 bara for H2, 0.5 to 5 bara for CO, and in the temperature range from 90 to 125 °C. Activation energies were determined for the individual reactions showing a shift in activation energy most significantly for the hydroformylation to n-pentanal for temperatures of 110 °C and above. For all substrates the effective reaction orders were calculated and employed in a power-law rate model giving good agreement of measured and modeled data within a ±20 % error margin. Similar results were obtained using a microkinetic model.
CRIS-Team Scopus Importer:2022-06-03
Keywords: diphosphite ligand; hydroformylation; immobilization; rhodium; supported catalysts